Music production management at SMA Negeri 1 Kanangan Kediri - Itot, Itot Bian Raharjo (Jurnal Abdimas Akademika, 2024)
Higher Education is a scientific institution that has the main task of implementing the Tri Dharma of Higher Education, namely education and teaching, research, and community service. Through the tasks it carries, it is hoped that the Higher Education Institution will become a center for the development of the whole human being as well as the maintenance and development of science, technology, and art in accordance with the needs both in the present and in the future. Similar to Higher Education, in order to implement the Tri Dharma of Higher Education – Community Service, various activities will be carried out in the form of "Music Production Training at SMA Negeri 1 Kandangan in Kediri". This training aims to introduce and implement vocal and recording techniques, which are expected to be the main provision for cultural arts teachers and students in developing music production, increasing professionalism in music (especially in presenting professional music), and can be a superior selling force in the local, regional, and even national scope. In facing the challenges of the music industry globally, by maximizing the potential of human resources optimally and following the development of today's technology.